Repeated Alliances Across Product Markets: The Formation and Performance Implications - Park, Sohyuun (My University, 2023)
This dissertation explores a phenomenon of market entry through cross-market repeated alliance, or market entry through repeated alliance with an existing partner from another product market. While it has been studied much how firms use its internal resources to enter a product market, relational resources have received little attention as valuable firm resources in market entry. Such lack of studies on the use of relational resources in market entry is surprising, considering that strategic alliance is an important strategic tool of firms. In this regard, in the first chapter, I examine when firms enter product markets through cross-market repeated alliances with existing partners rather than find new partners. Furthermore, the second chapter studies the performance implications of such cross-market repeated alliances in market entry. I study these questions in the context of the U.S. pharmaceutical industry where there are 15 distinct therapeutic areas. I configure a fine-grained dataset on alliance activities, drug development activities, and patents of firms in the U.S pharmaceutical industry from 1986 to 2019. I find that the cross-market repeated alliance is a salient phenomenon that bears attention. Firms use cross-market repeated alliances in market entry not only to successfully expand their corporate scope, but also to solidify their existing collaborations in other product markets. Cross-market repeated alliance is also a more efficient way to innovate compared to new partner alliance. These findings highlight the importance of relational resources in market entry and extend our understandings on repeated alliances by identifying the product markets of alliances.
University of Minnesota Ph.D. dissertation. 2023. Major: Business Administration. Advisors: Aks Zaheer, Aseem Kaul. 1 computer file (PDF); vi, 102 pages.
Keywords: Collaboration; Drug development; Market entry; Organizational behavior; Pharmaceutical industry; Strategic alliances